Bidirectional effect of earthquake on low-rise RC frames with and without the consideration of In-plane effect of unreinforced masonry infill. (January 2023) - Uprety, Rupesh; Suwal, Rajan
Abstract: Low rise RC frames make up the majority of residential structures built in Nepal. They are created in accordance with the requirements outlined in the Nepal Building Code, particularly the mandatory rule of thumb. Only the bare frame model is taken into consideration while analyzing and designing the majority of reinforced concrete structures in Nepal's urban and semi-urban areas. The infill walls' additional impact is often completely disregarded. Furthermore, there are no separate guidelines and standards set by Nepal Building codes for considering the impact of infill masonry during the analysis. Hence, in this study, reinforced concrete frame structures that commonly represent Nepalese low-rise RC frames is subjected to bidirectional (XY) shaking. Four types of models are considered and for each model, two cases are taken: those with and those without taking into account the in-plane effect of unreinforced masonry infill. The infills' in-plane impact is modeled using a macro modeling approach. The response parameters under investigation are column rebar strain ductility and roof displacement. The results of the analysis clearly indicate that, when the infills' in-plane effect is taken into account, both the roof displacement and the strain ductility demand of the column are greatly reduced as compared to the situation where it is not. Furthermore, it is obvious from the analytical fragility curves produced for the bare frame and infill models that the structure's vulnerability is exaggerated when the in-plane impact of infill is ignored.